Foodborne Pathogenic Vibrios: Antimicrobial Resistance - Dutta, Dipanjan; Kaushik, Anupam; Kumar, Dhirendra; Bag, Satyabrata (Frontiers in Microbiology, 2021)
Foodborne illness caused by pathogenic Vibrios is generally associated with the consumption of raw or undercooked seafood. Fish and other seafood can be contaminated with Vibrio species, natural inhabitants of the marine, estuarine, and freshwater environment. Pathogenic Vibrios of major public health concerns are Vibrio cholerae, Vibrio parahaemolyticus, and Vibrio vulnificus. Common symptoms of foodborne Vibrio infection include watery diarrhea, stomach cramping, nausea, vomiting, fever, and chills. Administration of oral or intravenous rehydration salts solution is the mainstay for the management of cholera, and antibiotics are also used to shorten the duration of diarrhea and to limit further transmission of the disease. The most commonly used antibiotics are the combination of a third-generation cephalosporin and tetracycline or a single-agent regimen with a fluoroquinolone or azithromycin. The emergence of antimicrobial resistance (AMR) in Vibrios is increasingly common across the globe and a decrease in the effectiveness of commonly available antibiotics poses a global threat to public health. Recent progress in comparative genomic studies suggests that the genomes of the drug-resistant Vibrios harbor mobile genetic elements like plasmids, integrating conjugative elements, superintegron, transposable elements, and insertion sequences, which are the major carriers of genetic determinants encoding antimicrobial resistance. These mobile genetic elements are highly dynamic and could potentially propagate to other bacteria through horizontal gene transfer. To combat the serious threat of rising AMR, it is crucial to develop strategies for robust surveillance, use of new/novel pharmaceuticals, and prevention of antibiotic misuse.